Kesehatan Mental Bagi Remaja: Workshop Mengenal dan Menjaga Kesehatan Mental Remaja - Triadi, Bagus Ficki; Kusumo, Purbo Jati; Evanavita, Putri; Rahmadani, Eliza Novia; Abdurrohman, Muhammad Maulana; Tauhida, Dina; Primadasa, Rangga (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Adolescent mental health is an important aspect that is often overlooked, even though adolescence is a critical phase in emotional and social development. The Adolescent Mental Health Workshop held in Purwodadi Village aims to increase adolescents' understanding of the importance of maintaining mental balance amidst academic and social pressures. This activity involves delivering interactive materials on signs of mental health disorders, stress management strategies, and how to seek support when facing psychological problems. The workshop results showed that adolescents in Purwodadi Village experienced a significant increase in their awareness of the importance of mental health. They were better able to recognize early symptoms of mental disorders and understand the importance of seeking support from family, friends, or professionals. The positive response from adolescents and support from posyandu cadres showed that this activity successfully built awareness of the importance of mental health in everyday life.